Aquaculture and Fisheries English Specific Purposes Students’: Needs Analysis Research - Sulistyawati, Anin Eka; Husain, Ahmad; E. Ivashova, Elizaveta (Universitas Pancasakti Tegal, 2022)
This research aims to determine the deficiency skills of ESP that need to be prioritized in the learning process of Aquaculture and Fisheries students. The methods used in this research are quantitative research with a questionnaire to measure their deficiency score and purposive sampling to take data into account precisely. However, the participant is not only from students but also from experts who have the expert insight of target learners in the occupation field. This research found that vocabulary and communication skills need to be prioritized in ESP learning for Aquaculture and Fisheries students, with a need score 2,9 and a lack score 2,6 for vocabulary skill and need score 2,5 and a lack score 2,2 for communication skills. In conclusion, participants are needed to master both of the skills to fulfill the occupation need forward. Then they also realize if it is difficult to master both of skills.